2014
DOI: 10.3390/ijerph120100146
|View full text |Cite
|
Sign up to set email alerts
|

Daily Physical Activity and Screen Time, but Not Other Sedentary Activities, Are Associated with Measures of Obesity during Childhood

Abstract: Childhood obesity is related to low physical activity level and a sedentary lifestyle. The aim of this study was to assess the physical activity level and sedentary behaviour of Malaysian children aged 7 to 12 years and to examine their association with body mass index (BMI), BMI-for-age Z-score (BAZ), body fatness (%BF) and waist circumference (WC). A total of 1736 children, representing all ethnic groups were recruited from six regions of Malaysia. Anthropometric measurements included body weight, height and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 53 publications
11
82
3
1
Order By: Relevance
“…Furthermore, physical activity outcomes were consistent with previous findings that the boys in the sample took more steps per day compared to girls [9,[15][16][17]. Boys had assessed and more engaged in neighborhood physical activity while girls participated in more passive activities like socializing, instead involved directly in physical activity [18].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, physical activity outcomes were consistent with previous findings that the boys in the sample took more steps per day compared to girls [9,[15][16][17]. Boys had assessed and more engaged in neighborhood physical activity while girls participated in more passive activities like socializing, instead involved directly in physical activity [18].…”
Section: Discussionsupporting
confidence: 79%
“…They were reported to have low percentage of meeting the recommended daily step counts cut off points (10.3% boys, 15.4% female) [14]. The averages detailed in the current study are most consistent with those reported in a large nationally representative sample of Malaysian children aged 7 to 12 years [9]. However, this sample of obese children was clearly more inactive when compared with other European studies, such as those from Ireland [15] and Greece [16] that have reported approximately 10000 to 13000 daily steps and was also less active than Australian obese children [17].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…12 Sedentary Behavior: D Sedentary Behavior was assigned a grade of D. It was reported that Malaysian children aged 7 to 12 years spent an average of 3.1 hours on screen-based activities (including television watching, video gaming, and computer use), 4 with only 31.6% of them meeting the screen time recommendation, that is, not more than 2 hours of recreational screen time per day. 14 School: B School was assigned a grade of B.…”
Section: Active Transportation: Dmentioning
confidence: 99%
“…The global analysis of combined data from the Global School-based Health Survey (GSHS) and the Health Behaviour in School-aged Children (HSBC) survey revealed that 80.3% of adolescents did not meet the PA recommendation of doing at least 60 minutes of moderate-to vigorous-intensity PA (MVPA) per day. 2 In Malaysia, findings from the Malaysian School-Based Nutrition Survey 2012 3 and Nutrition Survey of Malaysian Children (SEANUTS Malaysia) 4 show that more than half the children and adolescents were classified as having low levels of PA 3,4 and high levels of sedentary behavior, 4 suggesting the need for immediate and effective approaches to tackle this "inactivity epidemic. "…”
mentioning
confidence: 99%